Suffixes in Competition: On the Use of -our and -or in Early Modern English - Calle Martín, Javier; Pacheco-Franco, Marta; Calle-Martín, Javier (Servicio de publicaciones, Universidad de Murcia, 2020)
This paper presents a corpus-driven analysis of the linguistic competition between the suffixes -our/-or in Early Modern English. It is conceived as a state of the art to provide an explanation of the development and distribution of these competing suffixes in Early Modern English. The study is based on the distribution of the most common set of words with alternative spellings in the period to investigate the development and the standardisation of the -our and -or groups. The study offers the quantitative distribution of the suffixes in the period corroborating the participation of phenomena such as linguistic extinction, specialisation, blocking and lexicalisation in the configuration of the contemporary morphological paradigm. The source of evidence comes from the corpus of Early English Books Online (Davies, 2017) for the period 1470–1690. In addition to this, the study also relies on sources such as the Evans Corpus (2011), the Corpus of Historical American English (Davies, 2010) and the Corpus of Contemporary American English (Davies, 2008).
Política de acceso abierto de la revista: https://revistas.um.es/ril/about/submissions
Keywords: Inglés moderno; Early Modern English; Morphology; Standardisation; Suffixes